Pinjaman Online dalam Perspektif Pasal 1320 KUHPerdata dan Hadits Riwayat Imam Bukhori No.2085 dan Imam Muslim No.1598 - Hidayatulloh, Tutur Nurul; Arifin, Tajul (Journal of Literature Review, 2025)
This study examines the growing phenomenon of online loans (pinjol) in Indonesia from two different legal perspectives: positive law through Article 1320 of the Civil Code concerning the valid conditions of an agreement, and Islamic law based on the Hadith Narrated by Imam Bukhori No.2085 and Imam Muslim No.1598 concerning the prohibition of usury. Analysis of the validity of online loans according to Article 1320 of the Civil Code shows that many pinjol services fulfill the elements of agreement, ability, and certain things, but often have problems with the elements of a lawful cause, especially related to very high interest. Meanwhile, from the perspective of the hadith narrated by Imam Bukhori and Imam Muslim, the practice of online loans with excessive interest is clearly included in the category of usury which is prohibited in Islam. This study concludes the importance of stricter regulation of online loans to ensure compliance with the legal aspects according to the Civil Code while paying attention to the principles of sharia economics, so that it can protect society from exploitative financial practices that are contrary to legal and religious norms.